(untitled) (Altre Modernità, 2022)
In May 2020, Giorgio Agamben, one the most influential Italian philosophers of his generation, wrote in a post published on the website of the Italian Institute for Philosophical Studies that all those professors who would agree “to submit to the new telematic dictatorship and to teach their courses only online are the perfect equivalent of those university professors who in 1931 swore allegiance to the Fascist regime.” Philosophers, as is well known, have cultivated the art of paradox since the time of Zeno. In a less apocalyptic vein than Agamben’s post, in this essay I suggest that teachers and students involved in digital teaching and learning don’t run the risk of turning into dangerous Blackshirts, but at worst they might turn into zoomanti (a neologism that could be roughly translated into English as “Zoomers,” but also a word that for many Italian readers is evocative of the phrase “anime purganti,” “the souls of Purgatory”). More specifically, drawing on my experience of teaching online classes in American literature at the University of Munich for three semesters in a row, I reflect on both the risks and opportunities arising from the radical reconfiguration of the relationship between knowledge production and technology triggered by the Covid pandemic.